Assessment of the relationship between water insecurity, hygiene practices, and incidence of diarrhea among children from rural households of the Menoua Division, West Cameroon - Carole Nounkeu; Joseph Kamgno; Jigna Dharod (AOSIS, 2019)
The objectives of a cross-sectional, semi-quantitative study were to: i) assess the prevalence of water insecurity and its association with water access-related behaviors such as time, distance, and sources of water; ii) identify major themes of concern raised in reference to anxiety, water quality/quantity, and perceived health risk domains of water insecurity, and; iii) examine the relationship between water insecurity, hygiene practices, and diarrhea lincidence among children in rural areas of the Menoua Division in the Western Region of Cameroon In-person interviews were conducted with 18 years or older women living with at least one child between 2 and 5 years old (n=134). Participants spent on average 17±12 minutes walking to a drinking water source. Prevalence of water insecurity was 58%, and it was associated with a lower hygiene score among caretakers, i.e., hygiene score of water secure: 9.2±1.2 vs. insecure: 8.2±2.2, F(1, 132)=8.096, P<0.01). Overall, the incidence of diarrhea among children was 18%, and it was significantly higher among water insecure house-holds (79%) compared with secure house-holds (21%, P=0.02). In conclusion, access to improved sources of water is an issue in rural areas. Addressing water insecurity is critical in promoting optimal health and development of children due to its association with poor hygiene practices among caretakers.